2019
DOI: 10.1016/j.drugalcdep.2019.01.032
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal drug exposure from infancy through emerging adulthood: Results from neuroimaging

Abstract: Prenatal drug exposure may have important repercussions across the lifespan for cognition and behavior. While alcohol is a recognized teratogen, the influences of other substances may also be substantial. The neural underpinnings of the influences of prenatal drug exposure have been examined using longitudinal approaches and multiple imaging techniques. Here we review the existing literature on the neural correlates of prenatal drug exposure. We focused the review on studies that have employed functional neuro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…Prenatal exposure to substances included in this analysis has been associated with adverse health outcomes, including preterm birth, sudden infant death syndrome, and preterm-related death (exposure to tobacco) (5); low birth weight (tobacco, marijuana) (5,6); and altered fetal brain development (tobacco, marijuana) (5)(6)(7)(8). A review of prenatal substance exposure and neuroimaging suggests that in utero exposure to substances other than alcohol, including marijuana, nicotine, cocaine, methamphetamine, opioids, or combinations of substances, is associated with long-term effects on cognition and with altered brain connectivity and white matter deficits (9).…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal exposure to substances included in this analysis has been associated with adverse health outcomes, including preterm birth, sudden infant death syndrome, and preterm-related death (exposure to tobacco) (5); low birth weight (tobacco, marijuana) (5,6); and altered fetal brain development (tobacco, marijuana) (5)(6)(7)(8). A review of prenatal substance exposure and neuroimaging suggests that in utero exposure to substances other than alcohol, including marijuana, nicotine, cocaine, methamphetamine, opioids, or combinations of substances, is associated with long-term effects on cognition and with altered brain connectivity and white matter deficits (9).…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal marijuana exposure has been associated with decreased problem solving, visual-motor coordination, visual analysis, decreased attention span and behavior problems in offspring 144. Visual evoked potentials have been shown to be delayed at 18 months of age, while susbequent neuroimaging of young adults aged 18–22 show functional MRI scan differences with increased effort required for executive function tasks 148. Prenatal cannabis exposure has been associated with adolescent vulnerabilities to psychopathology, sleep problems, lower cognition and lower gray matter volume, providing more evidence of long term effects in the offspring 149 150…”
Section: Methodsmentioning
confidence: 99%
“…Although scarce, existing human studies of PDE effects point toward significant disruptions in distributed brain regions and circuits (Derauf, Kekatpure, Neyzi, Lester, & Kosofsky, 2009; Morie, Crowley, Mayes, & Potenza, 2019; Ross et al, 2015). For example, our previous studies on prenatal cocaine exposure reported reduced prefrontal volume (Grewen et al, 2014), aberrant functional connectivity (FC) between the medial prefrontal cortex and the amygdala (Salzwedel et al, 2015), as well as disrupted thalamus connectivity to different cortical targets (Salzwedel, Grewen, Goldman, & Gao, 2016).…”
Section: Introductionmentioning
confidence: 99%